Identification of Golovinomyces artemisiae Causing Powdery Mildew, Changes in Chlorophyll Fluorescence Parameters, and Antioxidant Levels in Artemisia selengensis - Guo, Zhixin; Sun, Xiaoyang; Qin, Ligang; Dong, Lili; Xiong, Liangbing; Xie, Fuchun; Qin, Dong; Chen, Yajun (Frontiers in Plant Science, 2022)
Artemisia selengensis Turcz is a valuable edible and medicinal vegetable crop widely cultivated in Northeast China. Powdery mildew (PM) disease occurs during field and greenhouse cultivation, resulting in production losses and quality deterioration. The pathogen in A. selengensis was Golovinomyces artemisiae identified using optical microscopic and scanning electron microscopic observations, morphological identification and molecular biological analyses. Parameters of chlorophyll fluorescence (ChlF) and antioxidant system responses as well as callose and lignin contents in A. selengensis were analyzed with inoculating G. artemisiae. Obvious photodamages of PM infected leaves were confirmed with significantly lower values in electron quantum transport rate (ETR), non-photochemical quenching (NPQ), photochemical quenching (qP), actual photochemical efficiency [Y(II)], but higher valued in non-adjusting energy dissipation yield [Y(NO)], supposed that Fv/Fm value and images could be used to monitor PM degree on infected A. selengensis. In addition, malondialdehyde (MDA), superoxide anion (O2∙-), callose, lignin contents and peroxidase (POD) activity increased while superoxide dismutase (SOD) activity, catalase (CAT) activity and ascorbic acid (AsA) content decreased significantly in infected leaves compared to mock-inoculated leaves, indicated that lignin and protective enzymes are the key indicators for detecting PM-resistant of A. selengensis. These results suggest that PM caused by G. artemisiae disrupted the photosynthetic capacity and induced imbalance of antioxidant system in A. selengensis. The findings were of great significance for designing a feasible approach to effectively prevent and control the PM disease in A. selengensis as well as in other vegetable crops.